The An Analysis Of Policy Planning For The Construction Of A Thousand Smooth Roads In Seluma Regency In 2021 - Pauzi Asri; Antonio Imanda; Evi Lorita (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
Abstrak